In vitro antibacterial activity and acute toxicity studies of aqueous-methanol extract of Sida rhombifolia Linn. (Malvaceae) - Pieme CA; Dzoyem JP; Assam JP Assam; Penlap VB (BMC, 2010)
Abstract Background Many bacteria among the Enterobacteria family are involved in infectious diseases and diarrhoea. Most of these bacteria become resistant to the most commonly used synthetic drugs in Cameroon. Natural substances seem to be an alternative to this problem. Thus the aim of this research was to investigate the in vitro antibacterial activity of the methanol and aqueous-methanol extracts of Sida rhombifolia Linn (Malvaceae) against seven pathogenic bacteria involved in diarrhoea. Acute toxicity of the most active extract was determined and major bioactive components were screened. Methods The agar disc diffusion and the agar dilution method were used for the determination of inhibition diameters and the Minimum Inhibitory Concentration (MICs) respectively. The acute toxicity study was performed according WHO protocol. Results The aqueous-methanol extract (1v:4v) was the most active with diameters of inhibition zones ranging from 8.7 - 23.6 mm, however at 200 μg/dic this activity was relatively weak compared to gentamycin. The MICs of the aqueous-methanol extract (1v:4v) varied from 49.40 to 78.30 μg/ml. Salmonella dysenteriae was the most sensitive (49.40 μg/ml). For the acute toxicity study, no deaths of rats were recorded. However, significant increase of some biochemical parameters such as aspartate amino-transferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and creatinine (CRT) were found. The phytochemical analysis of the aqueous methanol extract indicated the presence of tannins, polyphenols, alkaloids, glycosides, flavonoids and saponins Conclusion The results showed that the aqueous-methanol extract of S. rhombifolia exhibited moderate antibacterial activity. Some toxic effects were found when rats received more than 8 g/kg bw of extract. Antibacterial; Enterobacteria; Acute toxicity; Phytochemical analysis